2023
DOI: 10.1111/nph.18657
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial alternative NADH dehydrogenases NDA1 and NDA2 promote survival of reoxygenation stress in Arabidopsis by safeguarding photosynthesis and limiting ROS generation

Abstract: Summary Plant submergence stress is a growing problem for global agriculture. During desubmergence, rising O2 concentrations meet a highly reduced mitochondrial electron transport chain (mETC) in the cells. This combination favors the generation of reactive oxygen species (ROS) by the mitochondria, which at excess can cause damage. The cellular mechanisms underpinning the management of reoxygenation stress are not fully understood. We investigated the role of alternative NADH dehydrogenases (NDs), as compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 109 publications
0
10
0
1
Order By: Relevance
“…Both corresponding gene products function by avoiding mitochondrial respiration’s energy-saving reactions. AOX1A has a function in acclimation to low temperatures and can attenuate ROS production [ 31 , 32 ], a limitation Of ROS production was also observed in NDA1 overexpressor lines [ 33 ]. Cytosolic fumarase 2 ( FUM2 ) was downregulated in Col-0 after 1 day of cold exposure and further repressed after 3 days of cold exposure ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both corresponding gene products function by avoiding mitochondrial respiration’s energy-saving reactions. AOX1A has a function in acclimation to low temperatures and can attenuate ROS production [ 31 , 32 ], a limitation Of ROS production was also observed in NDA1 overexpressor lines [ 33 ]. Cytosolic fumarase 2 ( FUM2 ) was downregulated in Col-0 after 1 day of cold exposure and further repressed after 3 days of cold exposure ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondrial genome encodes few of the proteins that are components of the electron transport chain complexes (Unseld et al, 1997). For mitochondrial biogenesis to occur, expression of ROS homeostasis (Jethva et al, 2023), and the down regulation of this gene in mutant suggesting possible role of NO in ROS homeostasis via regulation of NDB1. Previously it was shown that mitochondrial glycine decarboxylase P protein which is important for redox balance was induced in response to NO (Palmieri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly important genes which are involved in mitochondrial metabolism such as NAD(P)H dehydrogenase B1 ( NDB1 ), Iron and NAD + transporter were also not upregulated during stress and recovery in mutants suggesting importance of COX6b, COA6‐L in mitochondrial metabolism during stress and recovery. NAD(P)H dehydrogenase B1 (NDB1) regulates ROS homeostasis (Jethva et al, 2023), and the down regulation of this gene in mutant suggesting possible role of NO in ROS homeostasis via regulation of NDB1. Previously it was shown that mitochondrial glycine decarboxylase P protein which is important for redox balance was induced in response to NO (Palmieri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This explains elevated ROS production in anac017 mutants due to the disrupted negative feedback loop. Simultaneous loss of function of NDA1 and NDA2 also resulted in enhanced ROS levels and, additionally, in a strong reduction of anoxia and submergence tolerance, and decreased photosystem II (PSII) efficiency upon reoxygenation (Jethva et al, 2023;Mittler, 2002;Umbach et al, 2005). Through uncoupling of mtETC from ATP production, UNCOUPLING PROTEIN 1 (UCP1) impedes extensive ROS generation, thereby preventing excessive reduction levels of mtETC proteins (Barreto et al, 2014(Barreto et al, , 2017(Barreto et al, , 2022.…”
Section: Flooding Stress Signalling and Adaptationmentioning
confidence: 99%
“…This explains elevated ROS production in anac017 mutants due to the disrupted negative feedback loop. Simultaneous loss of function of NDA1 and NDA2 also resulted in enhanced ROS levels and, additionally, in a strong reduction of anoxia and submergence tolerance, and decreased photosystem II (PSII) efficiency upon reoxygenation (Jethva et al., 2023; Mittler, 2002; Umbach et al., 2005).…”
Section: Flooding Stress Signalling and Adaptationmentioning
confidence: 99%